2011
DOI: 10.4103/0970-2113.76293
|View full text |Cite
|
Sign up to set email alerts
|

A study on habits of tobacco use among medical and non-medical students of Kolkata

Abstract: Background:Age-old practice “using tobacco” is a well known major global concern as it victimizes all its lovers by a host of chronic noncommunicable diseases including cancer; all develop very slowly and silently, and can cause premature death.Objectives:To assess the pattern of tobacco use among the medical and nonmedical college students.Materials and Methods:A cross-sectional descriptive study was carried out in Kolkata collecting anonymous data from 515 medical and 349 nonmedical college students of two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 6 publications
(11 reference statements)
3
16
4
Order By: Relevance
“…In other words, the lifetime prevalence of cigarette use among female students was almost equal to the prevalence of daily cigarette use among male students. This was observed in the previously conducted studies in Iran as well as those conducted in other countries (4,5,28). For example, the overall prevalence of daily cigarette use was 7% among students of dentistry, while the gender- specific rates were 3% and 12% for female and male students, respectively (28).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In other words, the lifetime prevalence of cigarette use among female students was almost equal to the prevalence of daily cigarette use among male students. This was observed in the previously conducted studies in Iran as well as those conducted in other countries (4,5,28). For example, the overall prevalence of daily cigarette use was 7% among students of dentistry, while the gender- specific rates were 3% and 12% for female and male students, respectively (28).…”
Section: Discussionsupporting
confidence: 81%
“…Overall, studies have indicated a higher prevalence of cigarette smoking among students of non-medical sciences. For example, Chaterjee et al reported that the last week prevalence of cigarette smoking in Kolkata (5), India, was 14.9% and 40.7% among students of medical and non-medical sciences, respectively. Another study conducted in Greece indicated corresponding values of 35.3% and 50.2% for the prevalence of current cigarette smoking (daily or occasional) (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this study showed that the management students were at greater risk of becoming smokers than the medical students. Several studies including in Nepal demonstrated that the smoking prevalence was higher among non-medical college students than the medical students [ 6 , 21 , 23 ]. A similar study in India also showed that exposure rate of tobacco was significantly higher among non-medical groups than medical groups (31 % vs. 10 %) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Comparison of medical students with nonmedical ones might be perfect in many conditions, but when there is a question of medical knowledge, the comparison of health education between these groups becomes mismatched. Medical students are enriched with medical knowledge, therefore they are all aware of health-related issues in detail, if not in depth.…”
mentioning
confidence: 99%